Walking back from the edge: thresholds of change reveal options for adaptation to water scarcity under climate change in the Murray–Darling Basin, Australia - Ellen Lesslie; Matthew J. Colloff; Jamie Pittock (Regional Environmental Change, 2023)
Climate change has increased the variability of river inflows in the Murray–Darling Basin, threatening the viability of irrigated agriculture, food processing industries and ecological condition of wetlands. With increasing water scarcity, decision-makers and communities face heightened contestation over scarce water resources and trade-offs and adaptation have become increasingly necessary. We used a social-ecological systems approach to identify thresholds of change in the Goulburn–Broken Catchment, a major food-producing region, to reveal options for adaptation to climate change. We developed systems models whereby feedbacks are identified between sub-systems of cultural paradigms, policies, human well-being and environmental condition. Models were constructed using data from semi-structured interviews with managers and decision-makers, industry reports and the scientific literature. We found environmental thresholds are fixed, but whether they are exceeded is socially determined. Environmental condition can be maintained by relaxing constraints on volumes of water released into the highly regulated river system and easing rules on the distribution of water among users in the dairy and horticulture industries. Socio-economic thresholds were more flexible. Industries have adapted to water scarcity through irrigation efficiency measures, inter-industry relationships for water-sharing and feed substitutes in dairy production. However, industry interdependence indicates potential for maladaption, whereas investment in adaptation and diversification offers more sustainable options. Current policy and management disconnects between water for the environment and water for food production reveal opportunities for co-benefits between environmental and socio-economic domains. Realising these benefits requires a systemic, inclusive adaptation pathways approach to design and implement options for change.